IMPROVING STUDENTS’ READING COMPREHENSION OF DESCRIPTIVE TEXT USING CIRC TECHNIQUE - Syamsul Anwar; Ruanda Januar (IKIP Siliwangi, 2018)
This research become performed in MA Al-Mukhtariyah Mande West Bandung. The objective of this research is used to investigate the implementation of CIRC technique in improving the students reading comprehension of descriptive text. The method used in this research was quantitative method. The design of the research was pre-experimental design. There are three steps involving pre-experimental design. The first step is the administration of pre-test measuring the dependent variable. The second step is the application of the experimental treatment (independent variable) to the subjects, and the final step is the administration of a posttest measuring the dependent variable again. It has seven times of conducting data, namely pretest, posttest, and five times treatments. Based on the result of pre-test, we observed that students’ reading comprehension is below average, the mean score of pre-test is 42.79. After the implementation of CIRC technique in every meetings, the students’ reading comprehension had been getting better, it is able to be seen in average of the mean score of post-test becam 73.82. It is able to be concluded that CIRC techniqiue can improve students’ reading comprehension. Keywords: Reading Comprehension, Descriptive Text, CIRC Technique